Bibliometrics characteristics on studies of anxiety and depression in university students during the COVID-19 pandemic - Balbuena Caballero, Clara Zenovia (2022)
The objective was to systematize the information on anxiety and depression during the COVID-19 pandemic in university students published in the PubMed database during the year 2020. 129 articles were analyzed whose variables were the following: number of authors, level of collaboration, country, journal of publication, associated topics, research approaches, sample size used, gender and age of the sample, language of publication and instruments used. The results found show that the number of average authors who sign a publication is 6; the countries that have published the most so far this year are China (26%) and the US (19%), in terms of factors related to anxiety and depression are stress, sleep-wake disorders, activity physical, loneliness and Post Traumatic Stress Disorder (PTSD), quantitative research approaches are the most used (97%), compared to qualitative and mixed (3%), the country that has worked with the largest samples is China with 746,217 people, the analyzed  articles present simples made up mostly of the female gender (86,8%), the most frequent average age is 20-21 years old (33.3%) all the articles are in English and the most used psychometric instrument has been the Generalized Anxiety Disorders Scale (GAD-7), the Patient Health Questionnaire (PHQ-9) and the Depression, Anxiety and Stress Scale (DASS-21). It is recommended to expand the analysis taking into account the year 2021 and include other data bases.